2011
DOI: 10.1136/bmj.d1542
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of glutamine, selenium, or both, to supplement parenteral nutrition for critically ill patients

Abstract: Objective To determine whether inclusion of glutamine, selenium, or both in a standard isonitrogenous, isocaloric preparation of parenteral nutrition influenced new infections and mortality among critically ill patients. Design Randomised, double blinded, factorial, controlled trial. Setting Level 2 and 3 (or combined) critical care units in Scotland. All 22 units were invited, and 10 participated. Participants 502 adults in intensive care units and high dependency units for ≥48 hours, with gastrointestinal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
182
0
13

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(198 citation statements)
references
References 27 publications
3
182
0
13
Order By: Relevance
“…6,7 However, recent large studies have not confirmed such an effect. 8,9 The objective of the present trial was to evaluate the effect of early glutamine and antioxidant supplementation in critically ill patients. Our a priori hypothesis was that supplementation with these nutrients would reduce 28-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 However, recent large studies have not confirmed such an effect. 8,9 The objective of the present trial was to evaluate the effect of early glutamine and antioxidant supplementation in critically ill patients. Our a priori hypothesis was that supplementation with these nutrients would reduce 28-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of critically ill patients with antioxidant nutrients, alone or in combination, is often referred to as "immune nutrition"; and has been studied in various, double-blind, randomized, placebo-controlled trials [83][84][85]. Although results from some of these trials were encouraging, the benefit of this therapy has not been clearly established.…”
Section: Antioxidant Nutrients In Neurocritical Carementioning
confidence: 99%
“…However, they did find that the evidence was more suggestive of a benefit on mortality in the first month for general ICU patients when compared with those with severe pancreatitis (p-value = 0.02). The more recent SIGNET trial 58 found that 500 μg selenium daily as part of PN in critically ill patients significantly decreased new infections in a subset of patients who received the supplement for ≥ 5 days, but it did not affect mortality. When the SIGNET trial data 58 for selenium supplementation were entered into the current Cochrane systematic review, 111 the random effects risk ratio for mortality changed from 0.75 (0.59-0.96, I 2 = 0%) to 0.86 (0.74-1, I 2 = 0%), and the risk ratio for new infections changed from 1.22 (0.67-2.23, I 2 = 0%) to 0.93 (0.79-1.09, I 2 = 0%).…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 99%
“…The more recent SIGNET trial 58 found that 500 μg selenium daily as part of PN in critically ill patients significantly decreased new infections in a subset of patients who received the supplement for ≥ 5 days, but it did not affect mortality. When the SIGNET trial data 58 for selenium supplementation were entered into the current Cochrane systematic review, 111 the random effects risk ratio for mortality changed from 0.75 (0.59-0.96, I 2 = 0%) to 0.86 (0.74-1, I 2 = 0%), and the risk ratio for new infections changed from 1.22 (0.67-2.23, I 2 = 0%) to 0.93 (0.79-1.09, I 2 = 0%). 111 In one older study, high-dose vitamin C administration during resuscitation (66 mg/kg/hour) was shown to attenuate lipid peroxidation and reduce resuscitation fluid requirements, as well as post-burn oedema.…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 99%
See 1 more Smart Citation